A systematic review of emerging trends in crop cultivation using soilless techniques for sustainable agriculture and food security in post-pandemic - Monsuru Adekunle Salisu, Siti Fairuz binti Yusoff (Tanjung Malim, 2024)
A systematic review of emerging trends in crop cultivation using soilless techniques for sustainable agriculture and food security in post-pandemic by Monsuru Adekunle Salisu, Siti Fairuz binti Yusoff